eCall++: improved emergency call - Gaztañaga, Jon Blancou (2017)
Thanks to the fast technological development and the pervasive adoption of personal electronic devices, e.g. smartphones, activity trackers, etc., with a multitude of sensors and communication protocols, some applications in the field of the Intelligent Transport Systems (ITS) can take advantage of such devices. For example, smartphones can be used for navigation, as driver interface for cooperative vehicular applications or even to detect accidents. Automated accident detection is a potential way to improve the road emergency services, thus decreasing the number of fatalities. For this purpose, the European Union (EU) has launched the eCall initiative, an automated accident detection and notification system, that will be mandatory for new cars in 2018. Legacy vehicles can also be retrofitted with eCall devices, that may require some wiring to install. An obvious solution, for legacy vehicles, is using the smartphone to detect accidents and disseminate emergency calls. A smartphone based accident detection algorithm and eCall application was already developed at Instituto de Telecomunicações in the scope of the HEADWAY project. However, this application, as the native eCall, missed to offer some important features, notably information on the number of passenger in the vehicle and a video stream of the accident site. This was the context behind the proposal presented in the dissertation. The eCall++ is a smartphone application that implements native eCall (accident detection and cellular network based emergency call), plus warning dissemination to vehicles in the vicinity of the accident site, based on ITS G5 communications. Additionally, the eCall++ application running on a vehicle that is involded in an accident also transmits to the emergency service the number of passengers in the car. An eCall++ application running on a car close to the accident site, but not involved in the accident, can be asked by the emergency service to transmit a video stream of the accident, using the vehicular network (ETSI ITS G5 communications). This will promote a better assistance to road vehicle crash location and to facilitate relevant information about traffic incidents to authorities. Due to privacy reasons it was decided not to use the camera of the vehicles involved in an accident.